[CO]EXISTENCE AS INTERSENSORIALITY IN THE SYMPHONIES OF HAVASI BALÁZS - BISCHIN, Maria-Roxana (Studia Universitatis Babes-Bolyai Musica, 2023)
We often wonder about piano music. And we're not just wondering because it fascinates us, but because it forces us to ask questions about life and the hidden senses of the sounds. For several times the music fills our lives. But how does it fill it? Many times a poem written by William Sharp or by Michael Shewmaker is a question for me as a philosopher. Furthermore, a composed song for piano by Havasi Balázs, makes us think a lot about a poem, or about anything which fascinates our mind. But despite the mind, there are many perceptions which work together to have a right judgement on the perception of the music. If we want to find how the music fulfills our lives with significances, we have to bring a phenomenological method in understanding these meanings. The phenomenology has an unique answer, because it finds out to answer to how the things (these phenomenological objects) are becoming. In this article we will show how the compositions of Havasi Balázs are up to date through the aesthetic sphere of the phenomenology and how they are entities in the phenomenological field of perception nowadays. For these reasons, it seemed essential to us to offer a phenomenological perspective to the symphonies realised by Havasi Balázs.